Factors associated with participation in colorectal cancer screening: a population-based study of 7200 Chinese individuals. Issue 1 (October 2019) - Huang, Junjie; Choi, Peter; Chen, Xiao; Wang, Jingxuan; Ding, Hanyue; Jin, Yinzi; Zheng, Zhi-Jie; Wong, Martin C S
Abstract: Background: Screening for colorectal cancer can reduce mortality, yet, participation rate is suboptimal in various countries. We aimed to evaluate the effectiveness of a pilot programme for colorectal cancer screening on increasing the enabling factors of screening in a large Chinese population, and identified factors associated with its participation based on variables pertinent to the Health Belief Model. Methods: We collected data from 3600 screening participants who were randomly selected using a telephone list for 2016, 2017, and 2018, from the government colorectal cancer screening programme. We also collected data from 3600 non-screening participants through a telephone survey via simple random sampling of telephone numbers in a territory-wide directory for the years 2016, 2017, and 2018. We collected sociodemographic factors, the enabling factors of screening (such as knowledge levels of colorectal cancer, perceptions of colorectal cancer screening, cues to actions), and barriers of screening. We constructed a logistic regression model to identify the association between these factors and participation in colorectal cancer screening adjusted for age, gender, educational level, and household income. The study was approved by the Joint Chinese University of Hong Kong − New Territories East Cluster Clinical Research Ethics Committee (reference number 2016.485). Verbal consent was obtained from the study participants. Findings: The knowledge level of colorectal cancer screening tools (from 67·9% to 85·4%, p<0·001), perceived severity of having colorectal cancer (from 37·7% to 42·8%, p<0·001), perceived benefits of screening (from 54·9% to 72·1%, p<0·001), and reductions in access barriers of colorectal cancer screening (from 18·5% to 7·5%, p<0·001) significantly improved from 2016 to 2018. People with older age (adjusted odds ratio [AOR] 2·02, 95% CI 1·77–2·30, p<0·001), higher level of knowledge of screening methods (6·70, 4·40–10·20, p<0·001), greater perceived severity (2·03, 1·69–2·43, p<0·001), and coverage of insurance (1·25, 1·09–1·43, p<0·01) were more likely to participate in screening. By contrast, more affluent people (0·68, 0·57–0·80, p<0·001), female individuals (0·64, 0·56–0·72, p<0·001), higher level of perceived psychological barriers (0·54, 0·42–0·69, p<0·001), and access barriers (0·57, 0·44–0·73, p<0·001) were associated with poorer participation. Interpretation: These findings demonstrate the effectiveness of the screening programme on increasing the enabling factors and identify the target groups such as younger individuals, females, and more affluent people among whom more intensive educational initiatives are needed to enhance their participation. Funding: Health and Medical Research Fund (No. 6904168), Food and Health Bureau, Hong Kong, China.